2006
DOI: 10.1158/0008-5472.can-05-2506
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of EGFR and ErbB2 by the Novel Dual EGFR and ErbB2 Tyrosine Kinase Inhibitor GW572016 Sensitizes Human Colon Carcinoma GEO Cells to Apoptosis

Abstract: Coexpression of the epidermal growth factor receptor (EGFR) family receptors is found in a subset of colon cancers, which may cooperatively promote cancer cell growth and survival, as heterodimerization is known to provide for diversification of signal transduction. Recently, efforts have been made to develop novel 4-anilinoquinazoline and pyridopyrimidine derivatives to inhibit EGFR and ErbB2 kinases simultaneously.In this study, we tested the efficacy of a novel reversible dual inhibitor GW572016 compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 45 publications
(52 reference statements)
1
56
0
Order By: Relevance
“…This suggests that either NTRK3 signaling is important for maintaining oocyte viability, or that AG 879 has a cytotoxic affect on oocytes in particular that is independent of its actions on the NTRK3 receptor. AG 879 has been shown to also inhibit signaling through the ERBB2 (neu) receptor (Levitzki & Gazit 1995, Zhou et al 2006, and ERBB2 receptor mRNA levels have been shown to be regulated during follicle development (Kezele et al 2005b). Therefore, it is possible that signaling through pathways other than that of NT3/NTRK3 are mediating this effect of oocyte loss.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that either NTRK3 signaling is important for maintaining oocyte viability, or that AG 879 has a cytotoxic affect on oocytes in particular that is independent of its actions on the NTRK3 receptor. AG 879 has been shown to also inhibit signaling through the ERBB2 (neu) receptor (Levitzki & Gazit 1995, Zhou et al 2006, and ERBB2 receptor mRNA levels have been shown to be regulated during follicle development (Kezele et al 2005b). Therefore, it is possible that signaling through pathways other than that of NT3/NTRK3 are mediating this effect of oocyte loss.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding colon cancer, Zhou et al reported that lapatinib (200 mg/kg daily) had significant antitumor activity compared to vehicle control. There was <10% weight loss compared to the vehicle control (41). These reports indicated that lapatinib at a dose of 200 mg/kg daily had a significant antitumor effect, but this dose seems to have severe drug toxicity.…”
Section: -------------------------------------------------mentioning
confidence: 95%
“…Heterodimers composed of ErbB-3 and a breast cancer-specific truncated form of ErbB-2 are also effectively inhibited by lapatinib (25). Lapatinib-mediated inhibition of ErbB-regulated signalling pathways in cell lines and in tumour xenografts resulted in partial cell cycle arrest and apoptosis (22,26,27). We and others have found that the effect of lapatinib on cell growth in various tumour cell lines is independent of ErbB-1/-2 expression levels (7,28,29).…”
Section: Introductionmentioning
confidence: 95%